The Effectiveness of Patrapottali Sveda, Thailadhara, and Panchathiktaka Ksheera Ghruta to Treat Osteoarthritis of Knee (Sandhivata) (International Journal of Ayurveda and Pharma Research, 2023)
Currently, arthritis is a throbbing illness that affects people all over the world. Osteoarthritis is the most common type of arthritis out of all the many variations. This is frequently observed in later stages of life. The effectiveness of Patrapottali sveda, Thailadhara for external administration, and Panchathiktaka ksheera ghruta for internal administration to treat osteoarthritis in the knee was investigated in light of the significant handicap caused by the condition. Methodology: In the present study 60 participants having osteo-arthritis of Knee and patients satisfying the inclusion criteria were recruited to the study. The total time period of the study was 60 days with 21 days of IP treatment and 24 days of OP treatment. The 21 days of treatment, included Valuka sveda for 1-3days followed by internal administration of Panchatiktaka ksheera kwatha and Panchatiktaka guggulu ghrita along with Pradesika Patrapottali sveda for 7 days along with internal medication Pradesika thaila dhara with Ketakeemooladi thaila was done, last 4 days, only internal medicines. Then in OP level for 24 days by the same internal medicines and application of Ketakeemooladi thaila on affected knee joint. The follow up for the completed cases were done after 15 days. Results and Conclusion: The responses of the treatment were satisfactory. The treatment results showed significant improvement in the functional ability of the patients. The functional parameters, VAS, WOMAC scale and SF36 showed significant improvement. The laboratory parameters used to evaluate the liver and kidney functions did not show any significant change that indicates the prescribed treatment is safe.